Investigation into patterns of epigenetic regulation of Alzheimer’s disease - Boden, Kirsty (2019)
Aberrant global and gene specific DNA methylation has been identified in late onset Alzheimer’s disease (LOAD) and has also been linked to its pathology. In addition, multiple loci associated with LOAD via genome wide association studies (GWAS) studies are being shown to harbour Alzheimer’s disease (AD) associated differential methylation in the LOAD brain. One aim of this thesis was to investigate if any differential methylation could be identified within the promoter regions of LOAD associated loci using leukocyte DNA, both for regions already identified as being aberrantly methylated in AD and those that have not been. This included the promoter regions of the genes INPP5D, SIRT1, HLA-DRB1/5, SORL1 and PTK2B. Of these genes only promoter methylation of INPP5D and SORL1 were identified in LOAD blood samples.